2020
DOI: 10.1038/s41467-020-15307-8
|View full text |Cite
|
Sign up to set email alerts
|

Electronic metal-support interactions in vacuum vs. electrolyte

Abstract: I n our communication 1 , we have investigated Pt nanoparticles supported on high surface area carbons (Pt/C) and boron carbide composites (Pt/BC). We showed that purely electronic interactions between the nanoparticulate catalyst and its support have bearings on electrocatalytic activity for the oxygen reduction reaction in acidic media and catalyst stability. This has been achieved by interrogating the electronic states of the supported Pt catalysts in an electrochemical environment via X-ray absorption near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Metal–support interactions play an important role in the improvement of the catalytic activity of supported metal catalysts. , In 2012, a new type of metal–support interaction, electronic metal–support interaction (EMSI), had attached increasing attention since it was first proposed by Campbell . Recently, much attention has been paid to the fabrication of novel catalysts by the EMSI effect. For example, Lu and his co-workers developed an atomical Au on two-dimensional VO 2 nanobelt catalysts for the efficient Fenton-like reaction . They concluded that the strong EMSI between Au atoms and VO 2 nanobelt supports could rapidly activate S 2 O 8 2– to generate SO 4 •– radicals to remove various recalcitrant organic pollutants; Datta et al realized the tuning of the EMSI between Ru nanoparticles and CuO nanowire supports by increasing multiple twinned Ru nanoparticle population, and they demonstrated that the defect-assisted EMSI could improve the catalyst activity and stability for oxygen evolution reaction at neutral condition; Wei’s group reported that EMSI from Co­(OH) 2 to Pt nanoparticles could form electron-rich Pt nanoparticles, leading to the improvement of the catalytic activity toward CO oxidation .…”
Section: Introductionmentioning
confidence: 99%
“…Metal–support interactions play an important role in the improvement of the catalytic activity of supported metal catalysts. , In 2012, a new type of metal–support interaction, electronic metal–support interaction (EMSI), had attached increasing attention since it was first proposed by Campbell . Recently, much attention has been paid to the fabrication of novel catalysts by the EMSI effect. For example, Lu and his co-workers developed an atomical Au on two-dimensional VO 2 nanobelt catalysts for the efficient Fenton-like reaction . They concluded that the strong EMSI between Au atoms and VO 2 nanobelt supports could rapidly activate S 2 O 8 2– to generate SO 4 •– radicals to remove various recalcitrant organic pollutants; Datta et al realized the tuning of the EMSI between Ru nanoparticles and CuO nanowire supports by increasing multiple twinned Ru nanoparticle population, and they demonstrated that the defect-assisted EMSI could improve the catalyst activity and stability for oxygen evolution reaction at neutral condition; Wei’s group reported that EMSI from Co­(OH) 2 to Pt nanoparticles could form electron-rich Pt nanoparticles, leading to the improvement of the catalytic activity toward CO oxidation .…”
Section: Introductionmentioning
confidence: 99%